PERIOSTEAL OSTEOSARCOMA PRESENTING IN JAW BONE; UNUSUAL SITE OF AN UNUSUAL ENTITY - Ghauri, Anam; Ghauri, Afifa (Journal of Ayub Medical College Abbottabad, 2025)
Periosteal osteosarcoma (PO) is a rare surface based bone tumor of intermediate grade, comprising mostly of chondroblastic tumor cells and accounts for 1-2% of all osteosarcoma cases. PO is almost often located in the long bones and affects patients mostly in their second and third decades of life. Mandible is a rare site. We report a rare case of mandibular periosteal osteosarcoma in a 26 year old female patient. She presented with fracture and swelling left side of mandible. Segmental mandibulectomy was performed. No pre surgical treatment was received. The radiological findings and histologic features led to the diagnosis of Periosteal osteosarcoma. There is no evidence of local recurrence after 05 months of follow up. This treatise highlights importance of radiological and histological identification of such an unusual entity at such unique primary site of occurrence.